Fulfillment of the Right to Education for Refugee Children in the East Java Immigration Area: A Human Rights Law Perspective - Alfi Syahrin; Siti Marwiyah; Moh. Taufik (Civiliza Publishing, 2026)
Refugee children are a vulnerable group who often face obstacles in accessing education, even though this right is guaranteed in various national regulations. This study examines the fulfillment of the right to education for refugee children in the working area of ​​the East Java Regional Office of the Directorate General of Immigration from a human rights law perspective. This study aims to determine the national legal regulations regarding the right to education for refugee children and the role of the Regional Immigration Office in ensuring it. The results show that although several regulations guarantee the right to education in general, there are no technical provisions that specifically regulate the rights of refugee children. The East Java Regional Immigration Office acts as a coordination facilitator, but still faces challenges such as limited documentation, lack of policy synchronization, and poor understanding of technical implementers. Affirmative policies and national technical guidelines are needed, as well as strengthened cross-sectoral coordination so that the right to education for refugee children can be fulfilled fairly and inclusively.